PP.58 Osteopathic Manipulative Treatment During Labour: An Exploratory Study. (26th April 2013) - Turi, P; Pizzolorusso, G; Matteo, A Di
Abstract : Objective: Osteopathic manipulative treatment (OMT) is an alternative medical practise that focuses on body health by treating the musculoskeletal framework. Its aim is to affect positively the body's nervous, circulatory and lymphatic systems [1]. To date, the use of OMT during labour has been limited [2, 3], although its effects are known during pregnancy [4, 5]. Aim: of this exploratory study is to investigate the effect of OMT in a group of women during labour. Methods: Of N = 119 women enrolled and in addition to ordinary care, N = 57 received OMT. Endpoints were differences in vaginal tears, Apgar scores and umbilical artery pH levels. Statistical analysis was based on multivariate regressions, focusing on the independent effect of OMT on primary outcomes. Results: Baseline characteristics were balanced in both groups. OMT (β –0.589; 95% CI –0.841 to –0.337; p < 0.0001) and episiotomy (β –1.053; 95% CI –1.334 to –0.773; p < 0.0001) were significantly associated with a reduction in vaginal tears. Only OMT was significantly associated to higher Apgar 1 min (β 0.572; 95% CI 0.240 to 0.903; p < 0.001) and 5 min scores (β 0.465; 95% CI 0.240 to 0.689; p < 0.0001). Risks factors for umbilical pH levels <7.35 were OMT (OR 0.363; 95% CI 0.149 to 0.848; p = 0.02) and women at second delivery (OR 0.346; 95% CI 0.129 to 0.918; p = 0.03). Conclusions: OMT during delivery was found to affect positively vaginal tears, Apgar scores and umbilical pH levels. References: Van Buskirk RL. Nociceptive reflexes and the somatic dysfunction: a model. J Am Osteopath Assoc 1990;792–4, 797–809. Whiting LM. Can the length of labour be shortened by osteopathic treatment? J Am Osteopath Assoc 1911;11:917–921. Hart LM. Obstetrical practise. J Am Osteopath Assoc 1918:609–614. Licciardone JC, Buchanan S, Hensel KL, King HH, Fuld KG, Stoll ST. Osteopathic manipulative treatment of back pain and related symptoms during pregnancy: a randomised controlled trial. Am J Obstet Gynecol 2010;202:43. King HH, Tettambel MA, Lockwood MD, Johnson KH, Arsenault DA, Quist R. Osteopathic manipulative treatment in prenatal care: a retrospective case control design study. J Am Osteopath Assoc 2003;103:577–582.